Effects of Ni irradiation on electron-phonon coupling and flux pinning in MgB2 film via Raman spectroscopy - Nhan, Duong T. T.; Pham, An T.; Le, Tien; Kang, Won-Nam; Tran, Dzung T.; Lee, Hong-Gu; Hwang, Jungseek; Nam, Nguyen Hoang (American Institute of Physics, 2025)
Effects of Ni-ion irradiation on the structural and flux-pinning properties of MgB2 films were investigated with particular importance on the role of Raman spectroscopy. MgB2 films (∼400 nm thick) were fabricated on c-cut Al2O3 substrates using a hybrid physicochemical vapor deposition technique and irradiated with 1 MeV Ni ions at doses ranging from 3 × 1013 to 9 × 1013 ions/cm2. X-ray diffraction (XRD) and Raman spectroscopy were examined to characterize the crystallinity and electron-phonon coupling (EPC) in the films, while magnetization measurements provided insights into the superconducting properties. The XRD results confirmed that all films were highly c-axis oriented, and the c-axis lattice constant slightly increased with increased Ni-ion dose. Raman spectra revealed significant changes in the E2g phonon mode, including shifts in peak positions and broadened FWHM (full-width at half-maximum), indicative of EPC degradation and the introduction of lattice disorder at an atomic scale. The decrease in the critical temperature (Tc) with increasing Ni-ion dose was correlated with these spectroscopic changes. The self-field critical current density (Jc) of the pristine MgB2 film was well maintained to be 4 × 106 A/cm2 at 20 K. Above the field of ∼2.5 T, the Jc was observed to clearly enhance and reach a maximum at a Ni-ion dose of 5 × 10¹³ ions/cm2, and Jc was maintained ∼103 A/cm2 at the field of ∼3.7 T. The observations might reveal the dominance of core point pinning, which resulted from the Ni-ion irradiation.